2022
DOI: 10.1186/s12886-022-02275-4
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hyaluronate combined with rhEGF contributes to alleviate clinical symptoms and Inflammation in patients with Xerophthalmia after cataract surgery

Abstract: Background To determine the effect of sodium hyaluronate combined with recombinant human epidermal growth factor (rhEGF) on clinical symptoms and inflammation in patients with newly diagnosed xerophthalmia after cataract surgery. Methods A total of 106 patients who underwent cataract surgery and were newly diagnosed with xerophthalmia in our hospital between June 2018 and August 2019 were enrolled. Of these, 50 patients who were treated with sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Even at very low doses, benzalkonium bromide, the most commonly used eye preservative, can cause inflammation in corneal epithelial cells, using artificial tears without preservatives. At present, there are few reports on the combination of sodium hyaluronate and rEGF without preservatives, and the therapeutic effect of the combination of sodium hyaluronate and rEGF in the elderly population with dry eyes is rarely reported [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Even at very low doses, benzalkonium bromide, the most commonly used eye preservative, can cause inflammation in corneal epithelial cells, using artificial tears without preservatives. At present, there are few reports on the combination of sodium hyaluronate and rEGF without preservatives, and the therapeutic effect of the combination of sodium hyaluronate and rEGF in the elderly population with dry eyes is rarely reported [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that when ocular diseases develop, the levels of IL-1, IL-6 and other factors were memorably elevated, and high levels of in ammatory factors might interfere with ocular surface homeostasis. With the aggravation of the disease, the levels of in ammatory factors in patients gradually increased, and were closely related to the clinical symptoms [20][21] . This work showed that the joint treatment signally reduced in ammatory response and promoted the improvement of dry eye syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current treatment approach needs to be clinically addressed to make up for the shortcomings of these therapies[ 7 , 8 ]. Recombinant human epidermal growth factor (rhEGF), a multifunctional growth factor that promotes tear secretion and lacrimal gland cell proliferation, improves the regeneration ability of corneal epithelial cells and shortens the repair time of damaged corneal tissues, thereby promoting the functional recovery of corneal endothelial cells[ 9 ].…”
Section: Introductionmentioning
confidence: 99%